THE IMPACT OF HEALTH EDUCATION USING FOCUS GROUP DISCUSSION ON BREAST SELF-EXAMINATION (BSE) BEHAVIOR AMONG FEMALE STUDENTS AT SMAN 14 MAKASSAR - Ratna sari; Mikawati; Evi lusiana; Muaningsih; Rizky pratiwi (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2025)
Breast cancer poses a significant global threat to women's health, yet awareness and practice of its most accessible early detection method—Breast Self-Examination (BSE)—remain low among adolescent girls, especially high school students. This study aims to examine the impact of health education using the Focus Group Discussion (FGD) method on BSE behavior among 11th-grade female students at SMAN 14 Makassar in 2023. A pre-experimental research design with a one-group pretest-posttest approach was employed. A total of 51 female students were selected through probability sampling. Data were collected using a standardized questionnaire assessing both knowledge and attitudes toward BSE. The Wilcoxon test revealed a significant increase in knowledge following the intervention (p = 0.001), indicating a meaningful difference between pretest and posttest scores. In contrast, although there was an increase in attitude scores post-intervention, the result was not statistically significant (p = 0.239). These findings suggest that while the health education intervention effectively improved knowledge about BSE, its influence on attitude change was not statistically confirmed. Nevertheless, the upward trend in attitude scores implies potential for long-term impact. In conclusion, health education through FGD proved to be effective in enhancing students’ knowledge of BSE and may contribute to fostering more positive attitudes over time. This highlights the importance of integrating structured health education programs into school curricula to promote early breast cancer prevention among adolescents.